1998
DOI: 10.1002/hlca.19980810302
|View full text |Cite
|
Sign up to set email alerts
|

Warum Pentose‐ und nicht Hexose‐Nucleinsäuren??. Teil V. (Purin‐Purin)‐Basenpaarung in der homo‐DNS‐Reihe: Guanin, Isoguanin, 2,6‐Diaminopurin und Xanthin

Abstract: This paper concludes the series of reports in this journal [l-41 o n the chemistry of homo-DNA, the constitutionally simplified model system of hexopyranosyl-(6' + 4)-oligonucleotide systems studied in our laboratory as potentially natural-nucleic-acid alternatives in the context of a chemical aetiology of nucleic-acid structure. The report describes the synthesis and pairing properties of homo-DNA oligonucleotides which contain as nucleobases exclusively purines, and gives, together with part 111 of the serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 135 publications
(99 reference statements)
2
53
0
8
Order By: Relevance
“…In our opinion, the possible participation of these tautomers in the interactions of iG should also be taken into consideration. The participation of the 2-oxo, N3-H, 6-amino tautomeric form (structure IV, Figure 4) in various base pairs involving iG was postulated by Eschenmoser and co-workers in order to explain the formation of complexes of various unnatural polynucleotides studied in their laboratory [32,33]. Isocytosine can exist in various tautomeric forms, however, the experimental and theoretical data are consistent with the fact that 1-substituted iC adopts the 2-amino-4-oxo form ( Figure 1A) in environments of intermediate to high polarity ( [31] and references cited therein).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our opinion, the possible participation of these tautomers in the interactions of iG should also be taken into consideration. The participation of the 2-oxo, N3-H, 6-amino tautomeric form (structure IV, Figure 4) in various base pairs involving iG was postulated by Eschenmoser and co-workers in order to explain the formation of complexes of various unnatural polynucleotides studied in their laboratory [32,33]. Isocytosine can exist in various tautomeric forms, however, the experimental and theoretical data are consistent with the fact that 1-substituted iC adopts the 2-amino-4-oxo form ( Figure 1A) in environments of intermediate to high polarity ( [31] and references cited therein).…”
Section: Discussionmentioning
confidence: 96%
“…We cannot exclude the participation of tautomers of iG, other than structures I and II (Figure 4), in its possible plenitude of interactions with natural and non-natural bases considered by the authors quoted above [30][31][32][33]. It is worth emphasizing that relevant experimental data on the structure of iG base-pairing are rather scarce [36], whereas the evaluations of the stability and geometry of base pairs are often just of a qualitative nature [31].…”
Section: Discussionmentioning
confidence: 98%
“…[225] Recent calculations have confirmed that formation of isoG quartets and isoG pentamers depends on the size of the templating cation. [229] Since isoG and G are self-complementary, [230,231] it is also possible that G and isoG may be able to form mixed assemblies. [232] In addition to the ligand and the cation, the anion may also affect the self-assembly of lipophilic nucleosides.…”
Section: G-quartets and Isog Pentamersmentioning
confidence: 98%
“…34,35 We therefore anticipated that no protection of the carbonyl in strH 5 would be required. Dimethoxytritylation of strH 5 provided the O5-protected derivative 28 (61%) that underwent phosphitylation at O3 using compound 29 and standard conditions to give the strH nucleoside phosphoramidite 30 (51%).…”
Section: Methodsmentioning
confidence: 99%